Autophagy-associated circular RNA hsa_circ_0007813 modulates human bladder cancer progression via hsa-miR-361-3p/IGF2R regulation - Zhang, Zheyu; Mou, Zezhong; Xu, Chenyang; Wu, Siqi; Dai, Xiyu; Chen, Xinan; Ou, Yuxi; Chen, Yiling; Yang, Chen; Jiang, Haowen (Cell death & disease, 2021)
Circular RNAs (circRNAs) drive several cellular processes including proliferation, survival, and differentiation. Here, we identified a circRNA hsa_circ_0007813, whose expression was upregulated in bladder cancer. High hsa_circ_0007813 expression was associated with larger tumor size, higher primary tumor T stage, and higher pathologic grade. Survival analysis showed that patients with high hsa_circ_0007813 expression levels had a poorer prognosis. Based on these findings from clinical tissue samples and cell lines, we assumed that hsa_circ_0007813 functioned a vital role in bladder cancer progression. Next, functional experiments revealed that knockdown of hsa_circ_0007813 inhibited proliferation, migration, and invasiveness of bladder cancer cells both in vitro and in vivo. Through extensive bioinformatic prediction and RNA pull-down assays, we identified hsa-miR-361-3p as a competing endogenous RNA of hsa_circ_0007813. Further bioinformatic studies narrowed targets to 35 possible downstream genes. We then found that knockdown of hsa_circ_0007813 led to altered cell autophagy, bringing our attention to IGF2R, one of the possible downstream genes. IGF2R was also known as cation-independent mannose-6-phosphate receptor (CI-M6PR), was discovered to participate in both autophagy and tumor biology. Regarding autophagy has a dominant role in the survival of tumor cells overcoming cellular stress and correlates with tumor progression, investigations were made to prove that hsa_circ_0007813 could regulate IGF2R expression via hsa-miR-361-3p sponging. The potential of hsa_circ_0007813 in regulating IGF2R expression explained its influence on cell behavior and clinical outcomes. Collectively, our data could offer new insight into the biology of circRNA in bladder cancer.